The Muhafadzoh Syiir Aqidatul Awwam book is being used to instill the ideals of Ahlussunah Wal Jama'ah in the Madrasah Diniyah Al-Istiqomah kids in Getrakmoyan Village, Cirebon Regency - Sentia; Dinardi, Dian; Alawiyah, Tuti (Departement of PAI, Universitas Majalengka, 2023)
Faith is the main tool used by believers to navigate the lessons that God gave to his messengers. Ideology, or aqidah, is unquestionably a highly significant concept. Furthermore, ahlussunah wal jama'ah is the finest example of aqidah. The majority of Muslims in Indonesia practice Islam according to ahlussunah wal Jama'ah, which emphasizes living in harmony with everyone. But extremist Islamic thinking groups have long fostered hostility toward anyone who is different from them, and there have been a number of voices discussing aqeedah recently. With the muhafadzoh syiir kitab aqidatul awwam program, Madrasah Diniyah Al-Istiqomah seeks to break through radical doctrines and inculcate the ideals of ahlussunah wal jama'ah. Madrasah Al-Istiqomah is one of the madrasahs that aims to develop students who have the ideals of ahlussunah wal jama'ah by introducing the principles of ahlussunah wal jama'ah to the basic level. Thus, one way to teach and inculcate in pupils a religious knowledge of ahlussunah wal jama'ah is through the muhafadzoh syiir kitab aqidatul awwam program. The researchers came to the conclusion that the planting of aswaja values through the muhafadzoh syiir kitab aqidatul awwam program for Madrasah Diniyah Al-Istiqomah Village Getrakmoyan Cirebon Regency by nadzoman together for about 10-15 minutes before starting to deposit.